2016
DOI: 10.1371/journal.pone.0156337
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of Concepcion Bank: Evidence of Geological and Biological Processes on a Large Volcanic Seamount of the Canary Islands Seamount Province

Abstract: Concepcion Bank is the largest seamount in the Canary Islands Seamount Province (CISP), an oceanic area off NW Africa including 16 main seamounts, the Canaries archipelago and the Selvagens subarchipelago. The Bank is located 90 km northeast of Lanzarote Island and has been identified as a candidate Marine Protected Area (MPA) to be included in the Natura 2000 network. A compilation of complementary datasets consisting of multibeam bathymetry, TOPAS seismic reflection profiles, side scan sonar sonographs, Remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 72 publications
0
9
0
1
Order By: Relevance
“…The crust in the easternmost islands of the Canary archipelago is 11-15 km thick (Banda et al, 1981). This area is located at the transition between continental and oceanic crust and is characterized by a 10-km-thick sediment layer east of the ridge (e.g., Rivera et al, 2016). The central seafloor surface of the Canary Channel extends between 1,240 m and 1,460 m water depth, and its most significant features are submarine hills of volcanic or diapiric origin (Acosta et al, 2005).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The crust in the easternmost islands of the Canary archipelago is 11-15 km thick (Banda et al, 1981). This area is located at the transition between continental and oceanic crust and is characterized by a 10-km-thick sediment layer east of the ridge (e.g., Rivera et al, 2016). The central seafloor surface of the Canary Channel extends between 1,240 m and 1,460 m water depth, and its most significant features are submarine hills of volcanic or diapiric origin (Acosta et al, 2005).…”
Section: Geological Settingmentioning
confidence: 99%
“…The central seafloor surface of the Canary Channel extends between 1,240 m and 1,460 m water depth, and its most significant features are submarine hills of volcanic or diapiric origin (Acosta et al, 2005). Along the Canary Channel, early Triassic evaporitic diapirs intrude Mesozoic sedimentary units and form mounds when they reach the seabed (Rivera et al, 2016). The diapir belt has gained the interest of oil companies for hydrocarbon exploration and it was the focus of the drilling activities monitored in this work.…”
Section: Geological Settingmentioning
confidence: 99%
“…This intense stratification is due to the density difference between the Atlantic and Mediterranean waters, which determines the stability of the water column. The associated high values of the Brunt-Väisälä frequency make the NACW-MOW interface an adequate area for the generation and propagation of internal waves, which after the interaction with the gentle slope of the seamounts, can end up breaking, and therefore enhancing the vertical mixing and producing upwelling (IUCN, 2013;Rivera et al, 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…can act as mixing agents enhancing particle resuspension and availability. Rivera et al (2016) recently suggested that particle resuspension can be induced locally by internal waves generated at depths of the NACW-AAIW confluence. This is fully consistent with the local increase of zooplankton: total biomass and copepod, cnidarian, or chaetognath biomass in our results at the NACW-AAIW confluence near 700 m ( Figure 6).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is fully consistent with the local increase of zooplankton: total biomass and copepod, cnidarian, or chaetognath biomass in our results at the NACW-AAIW confluence near 700 m ( Figure 6). Also, internal waves are mainly generated to the SW of the bank (Rivera et al, 2016), due to optimal inclination of the seamount flanks. This area coincided with the location of NACW-AAIW hauls at Concepción Bank (Figures 6 and 8).…”
Section: Accepted Manuscriptmentioning
confidence: 99%